2013
DOI: 10.1126/science.1238724
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of an RNA Polymerase II Transcription Pre-Initiation Complex

Abstract: Summary The protein density and arrangement of subunits of a complete, 31-protein, RNA polymerase II (pol II) transcription pre-initiation complex (PIC) were determined by cryo-electron microscopy and a combination of chemical cross-linking and mass spectrometry. The PIC showed a marked division in two parts, one containing all the general transcription factors (GTFs), and the other pol II. Promoter DNA was associated only with the GTFs, suspended above the pol II cleft and not in contact with pol II. This str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
134
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(149 citation statements)
references
References 64 publications
(97 reference statements)
11
134
0
2
Order By: Relevance
“…Furthermore, the C‐terminal cyclin domain of Rrn7 is not positioned as closely to the DNA as in Pol II, where the C‐terminal cyclin domain of TFIIB contacts DNA upstream of the TATA box (Plaschka et al , 2016). The observed differences could be a result of DNA bending by TBP in the Pol II PIC, which brings the DNA in close proximity to the C‐terminal cyclin domain (Murakami et al , 2013, 2015; Plaschka et al , 2015, 2016; He et al , 2016). Nevertheless, the overall conformation of the C‐terminal cyclin domain relative to the N‐terminal cyclin domain is conserved between TFIIB‐like factors (Fig 3C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the C‐terminal cyclin domain of Rrn7 is not positioned as closely to the DNA as in Pol II, where the C‐terminal cyclin domain of TFIIB contacts DNA upstream of the TATA box (Plaschka et al , 2016). The observed differences could be a result of DNA bending by TBP in the Pol II PIC, which brings the DNA in close proximity to the C‐terminal cyclin domain (Murakami et al , 2013, 2015; Plaschka et al , 2015, 2016; He et al , 2016). Nevertheless, the overall conformation of the C‐terminal cyclin domain relative to the N‐terminal cyclin domain is conserved between TFIIB‐like factors (Fig 3C).…”
Section: Resultsmentioning
confidence: 99%
“…Pol I contributes more than 60% to the total cellular transcription activity of the cell and accordingly requires high transcription initiation rates (Schneider, 2012). During transcription initiation, Pol I, similar to other eukaryotic RNA polymerases, assembles together with its specific transcription factors on the ribosomal RNA promoter to form the pre‐initiation complex (PIC; Murakami et al , 2013). In sequential steps, the PIC transitions from a closed complex (CC), in which the DNA is still double‐stranded, to an open complex (OC), in which the double‐stranded DNA in the vicinity of the transcription start site is melted.…”
Section: Introductionmentioning
confidence: 99%
“…This includes information about the subunit organization of the polymerases themselves as well as the organization of polymerases with additional proteins into higher-order functional units. Studies have targeted RNA Pol I [81,82], II [83], and III [84] as well as the Pol II-PIC complex [85,86] and the Pol II-capping enzyme complex [87]. A subcomplex of the Mediator complex (the so-called middle module) [88] and the Mediator head module in complex with the C-terminal domain of Pol II [89] were also investigated by XL-MS. More recently, XL-MS was used to provide spatial restraints on the Mediator core and the Pol II-Mediator core initiation complex in the most comprehensive study on polymerases and associated complexes to date [90].…”
Section: Ribosomes and Associated Proteinsmentioning
confidence: 99%
“…Indeed, today we understand the regulation of Pol II initiation by the general transcription factors (GTFs) at a detailed molecular level. 1,2 During the past several years, biochemical and genomic analyses have revealed that Pol II recruitment is not the only point of transcriptional regulation. Rather, the transition between initiation and elongation is a multi-step process where any point between recruitment and productive elongation can potentially be regulated for proper gene expression in eukaryotes.…”
Section: Introductionmentioning
confidence: 99%